Influence of Hypoglycemia During The 100-G Oral Glucose Tolerance Test on Obstetrics Outcomes - İnegöl Gümüş, İlknur; Karakurt, Feridun; Kargılı, Ayşe; Carda Seçkin, Neslihan; Kafalı, Hasan; Öztürk Turhan, Nilgün (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVES: We aimed to investigate the impact of hypoglycemia during 100-g oral glucose tolerance test on perinatal outcomes. STUDY DESIGN: Obstetrics records of 411 pregnants who delivered singletons at our institution were reviewed. 31/411 (7,5 %) of patients who were diagnosed as Gestational Diabetes Mellitus were excluded from the study. The study group was consisted of pregnant women who experienced hypoglycemia defined as a plasma glucose level of 60 mg/dL or less during the 100-g oral glucose tolerance test. This group were compared with women who had normal glucose levels during 50-g oral glucose loading test (glucose challenge test) and who had normal values and had no hypoglycemia during 100-g OGTT. RESULTS: We identified 62 hypoglycemic patients (15 %) on 100-g oral glucose tolerance test and 318 non-hypoglycemic patients (77,3 %) as control group. Gestational weight gain was statistically higher in hypoglycemic group. The mean birth weight was 3419±421,9 g in the study group and 3275±491,7 g in the control group (p=0.042). Rates of babies admitted to NICU were similar in both groups. CONCLUSIONS: Women who experience hypoglycemia during the OGTT have a significantly higher incidence of gestational weight gain and higher neonatal birth weights as well. As a result if a pregnant has hypoglycemia during OGTT we should monitorize her and the fetus as well carefully.